Employer Attractiveness From an Employee Perspective: A Systematic Literature Review - Dassler, Anke; Khapova, Svetlana N.; Lysova, Evgenia I.; Korotov, Konstantin (Frontiers in Psychology, 2022)
With the growing interest in employer attractiveness, research is unsystematic on how this phenomenon can be conceptualized and studied. Studies tend to make little conceptual differentiation regarding for whom employers should be attractive, and therefore, address the perspectives of potential as well as current employees, who work in organizations for long periods of time. In this study our arguments relate to the phenomenon’s conceptual clarity as well as its differentiation from other related concepts. By focusing on employer attractiveness for current employees, we have systematically reviewed 48 studies published in business and management journals, and categorized findings into the Inputs-Mediators-Outputs model. This approach allowed us to depict significant limitations in the existing knowledge about employer attractiveness from the current employees’ perspective, and offer avenues for future research. Next, to delineate the future research agenda, we have concluded this study with a discussion on what our findings mean for managers and organizations.